Phagocytosis‐related NADPH oxidase 2 subunit gp91phox contributes to neurodegeneration after repeated systemic challenge with lipopolysaccharides. Issue 1 (28th July 2020) - Shahraz, Anahita; Wißfeld, Jannis; Ginolhac, Aurélien; Mathews, Mona; Sinkkonen, Lasse; Neumann, Harald
Abstract: Repeated systemic challenge with lipopolysaccharides (LPS) can induce microglia activation and inflammatory neurodegeneration in the substantia nigra pars compacta region of mice. We now explored the role of mononuclear phagocytes associated nicotinamide adenine dinucleotide phosphate oxidase 2 (NOX‐2) in inflammatory neurodegeneration. Cybb ‐deficient NOX‐2 knock‐out (KO) and control wild type (WT) mice were treated intraperitoneally daily over four consecutive days with 1 μg/gbw/day LPS. Transcriptome analysis by RNA‐seq of total brain tissue indicated increased LPS‐induced upregulation of genes belonging to the reactive oxygen species and reactive nitrogen species production, complement and lysosome activation as well as apoptosis and necroptosis in WT compared to NOX‐2 KO mice. Validation of up‐regulated gene transcripts via qRT‐PCR confirmed that LPS‐challenged NOX‐2 KO mice expressed lower levels of the microglial phagocytosis‐related genes Nos2, Cd68, Aif1/Iba1, Cyba, Itgam, and Fcer1g compared to WT mice at Day 5 after systemic inflammatory challenge, but no significant differences in the pro‐inflammatory genes Tnfα and Il1b as well as microglial IBA1 and CD68 intensities were observed between both genotypes. Furthermore, loss of tyrosine hydroxylase positive (TH+) and NeuN positive neurons in the substantia nigra pars compacta upon repeated systemic LPS application were attenuated in NOX‐2 KO mice. Thus, our data demonstrate that loss of dopaminergic neurons in the substantia nigra pars compacta after repeated systemic challenge with LPS is associated with a microglial phagocytosis‐related gene activation profile involving the NADPH oxidase subunit Cybb/gp91phox. Main Points: Loss of neurons in the substantia nigra pars compacta upon repeated systemic application of LPS was attenuated in NOX‐2 KO compared to WT control mice. Complement, phagocytosis/lysosome and necroptosis/apoptosis are the major involved pathways.